PROJECT-BASED LEARNING AS A TOOL FOR IMPROVING ENGLISH COMMUNICATION SKILLS - Behruzkhon Yuldoshev Behzod ugli (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores the role of Project-Based Learning (PBL) in enhancing English communication skills among learners. PBL, an instructional approach that involves students in collaborative, real-world projects, has gained recognition as an effective method for developing both linguistic competence and critical thinking. By engaging in authentic tasks, learners improve their speaking, writing, listening, and interpersonal communication in English. The article discusses the benefits, challenges, and practical strategies for implementing PBL in English language classrooms.